Modeling the pulsed neutron response for natural hydrogen detection - Xili, Xi; Qian, Chen; Feng, Zhang (Frontiers in Earth Science, 2025)
Hydrogen gas is a promising clean-energy vector that can alleviate the current imbalance between energy supply and demand, diversify the energy portfolio, and underpin the sustainable development of oil and gas resources. This study pinpoints the factors that govern hydrogen quantification by pulsed-neutron logging. Monte Carlo simulations were performed to map the spatial distribution of capture γ-rays in formations saturated with either water or hydrogen and to systematically assess the effects of pore-fluid composition, hydrogen density, gas saturation, lithology, and borehole-fluid type. The results show that the counts of capture γ-rays are litter in hydrogen-bearing formations. For low-to moderate-porosity rocks, the dynamic response window for hydrogen-saturated pores is approximately 10% wider than that for methane-saturated pores. Increasing hydrogen density or decreasing gas saturation raises the capture-γ ratio while narrowing the dynamic range. Changes in borehole fluid substantially affect the capture-γ ratio yet have only a minor impact on the dynamic range. Lithology imposes an additional control: serpentinite, enriched in structural water, generates markedly higher capture-γ ratios that may complicate the quantitative evaluation of hydrogen.